IL-21 shapes the B cell response in a context-dependent manner - Youngjun Kim; Francesca Manara; Simon Grassmann; Kalina T. Belcheva; Kanelly Reyes; Hyunu Kim; Stephanie Downs-Canner; William T. Yewdell; Joseph C. Sun; Jayanta Chaudhuri (Cell Reports)
Summary: The T-cell-derived cytokine IL-21 is crucial for germinal center (GC) responses, but its precise role in B cell function has remained elusive. Using IL-21 receptor (Il21r) conditional knockout mice and ex vivo culture systems, we demonstrate that IL-21 has dual effects on B cells. While IL-21 induced apoptosis in a STAT3-dependent manner in naive B cells, it promoted the robust proliferation of pre-activated B cells, particularly IgG1+ B cells. In vivo, B-cell-specific Il21r deletion impaired IgG1 responses post-immunization and disrupted progression from pre-GC to GC states. Although Il21r deficiency did not affect the proportion of IgG1+ cells among GC B cells, it greatly diminished the proportion of IgG1+ cells among the plasmablast/plasma cell population. Collectively, our findings suggest that IL-21 serves as a critical regulator of B cell fates, influencing B cell apoptosis and proliferation in a context-dependent manner.